Good Corporate Governance, Sustainability Disclosure, and Firm Performance: Evidence from Indonesia - ., Suharyono; Zarefar, Arumega; Astuti, Dwi; Sunarto, Nazrantika (Journal of Cultural Analysis and Social Change, 2025)
This study aims to comprehensively and in-depth examine the influence of good corporate governance (GCG) and sustainability disclosure on firm performance. The research hypotheses are tested using a panel data regression approach. The study sample comprised non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2022, totalling 972 firm-year observations. This study finds that GCG and sustainability disclosure significantly positively affect firm performance. Furthermore, we conducted additional analysis separating young and older firms, and the results are consistent with the main findings. This study's initial contribution is to integrate the important pillars of corporate sustainability, consisting of GCG and sustainability disclosure, into a single model to influence firm performance in Indonesia. This study expands the study of differences in corporate governance between developing and developed countries. Finally, this study introduces a new dimension by analysing company development stages based on age.